Molecular identification of Trichinella species by multiplex PCR: new insight for Trichinella murrelli - Karadjian Grégory; Heckmann Aurélie; Rosa Giuseppe La; Pozio Edoardo; Boireau Pascal; Vallée Isabelle (Parasite, 2017)
In order to identify Trichinella at the species level, the commonly used test is a multiplex PCR, allowing the discrimination of nine out of the twelve taxa described so far. This test is based on five primer pairs amplifying fragments of the large subunit rDNA. Each taxon produces one or two bands of different sizes, resulting in a specific band pattern. By multiplex PCR, Trichinella murrelli shows two bands of 127 bp and 316 bp. However, a third band of 256 bp can occur. This band can lead to misidentification, since it is similar to the 253 bp band displayed by Trichinella britovi. BLAST analysis confirmed that the 256 bp band is from T. murrelli. The aim of this short note is to inform analysts that T. murrelli larvae may display either two- or three-band patterns.